A case of primary extraskeletal osteosarcoma of the breast - Kanako Kurata; Keisei Anan; Nami Ishikawa; Kenichiro Koga; Michiyo Saimura; Kazuyoshi Nishihara; Toshimitsu Iwashita; Shoshu Mitsuyama; Sadafumi Tamiya; Hideyuki Watanabe; Yutaka Koga; Hidetaka Yamamoto; et al. (Surgical Case Reports, 2018)
Abstract Background Primary sarcomas of the breast are rare and account for less than 1% of all primary breast malignancies. We experienced a case of extraskeletal osteosarcoma of the breast that had a unique clinical course and remarkable findings of mammography and magnetic resonance imaging (MRI). A review of the case reports published in the past few decades showed no reports of a case in which a calcified lesion was followed up three different times on mammography, making this a valuable case report. Case presentation A 52-year-old woman noticed a right breast mass and underwent a breast examination. Mammography showed a 1.5-cm coarse calcified lesion in the upper outer portion of the right breast. Because fine-needle aspiration (FNA) revealed no suspicion of malignancy, she was followed up. Sixteen months later, the tumor grew progressively to 4.5 cm in size with new calcifications that were fine and irregular in shape and density surrounding an enlarged, coarse calcified lesion. Contrast-enhanced magnetic resonance imaging (MRI) showed a high signal intensity in the periphery of the tumor. Extirpation of the tumor was indicated. The pathological findings were extraskeletal osteosarcoma. She underwent additional resection and latissimus dorsi flap reconstruction at the Department of Orthopedic Surgery. Conclusion The present case suggests that mammography findings of a tumor with coarse calcifications that are not typical of benign lesions may be extraskeletal osteosarcoma. A diagnosis must be made as early as possible in order to improve the prognosis of this disease.